If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x-4)+3x=-3(x-8)
We move all terms to the left:
3(2x-4)+3x-(-3(x-8))=0
We add all the numbers together, and all the variables
3x+3(2x-4)-(-3(x-8))=0
We multiply parentheses
3x+6x-(-3(x-8))-12=0
We calculate terms in parentheses: -(-3(x-8)), so:We add all the numbers together, and all the variables
-3(x-8)
We multiply parentheses
-3x+24
Back to the equation:
-(-3x+24)
9x-(-3x+24)-12=0
We get rid of parentheses
9x+3x-24-12=0
We add all the numbers together, and all the variables
12x-36=0
We move all terms containing x to the left, all other terms to the right
12x=36
x=36/12
x=3
| -6.5+x=18.7 | | 1+8x=11+2x | | 9-(x+6)=4x-2 | | 2(x+5=3x+1 | | 6x-2=1/2x+9 | | 4(3n-5)=12n-20 | | 9-(x+6)=4x+2 | | 21+x=94 | | -45x^2-27=0 | | 81−46=x=-50 | | 2/y-3=3/6 | | (4x-5)-2x=0 | | x/19=8/570 | | 10^4^x=16 | | 9x-6+82+6x-1=180 | | 18x-7=29×7 | | -40n+48=9 | | .08x+x=3725 | | 1+x=72 | | 2(3x-5)=76 | | 3/x^2-4/5x=2/7 | | 42-2=2x | | 5(x-6)+x=30 | | 64+x=82 | | 3/4+4m/3=29/12 | | x(x+2)+2(x-6)=0 | | x-26=73 | | 5.7x+225=32.49+15x | | 25=9-8y | | 154=15x+x^2 | | 1.03x=7.21 | | 60xX-110=130 |